Efektivitas Pembelajaran Matematika Model Mind Mapping dan Make A Match terhadap Kemampuan Berfikir Kritis Siswa - Machromah, Isnaeni Umi; Efendi, Muhamad Taufiq (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to determine the effectiveness of the mind mapping learning model in mathematics learning and to measure the critical thinking skills of eighth-grade students at SMP Negeri 1 Gondang. This study employed quantitative research. The research method used was a quasi-experimental method. The data sources were 64 students in grades VIII B and VIII C. The results of the data analysis indicate that the mind mapping learning model has an effect on students' critical thinking skills, as indicated by an n-gain score of 83%, which is considered high. Meanwhile, the n-gain score for the make-a-match class was 73%, which can be considered high. Conclusion: There are differences between the mind mapping and make-a-match models, with the mind mapping model having a better effect than the make-a-match model.   Keywords: Mind mapping, Make a match, n-gain score